Language in society in Bangladesh and beyond : voices of the unheard in the Global South - Sultana, Shaila; Naushaad Kabir, Mian Md; Haider, Md Zulfeqar; Roshid, M. Moninoor; Hamid, M. Obaidul (Routledge studies in sociolinguistics., 2024)
"This collection presents a holistic picture of the sociolinguistic landscape in Bangladesh, offering a critical understanding of language ideologies and social inequalities in the country and as they connect more widely to dynamics in the Global South. The book seeks to untangle the voices embedded in the language practices of a range of communities and professions in the region, which have been little studied in the literature, and encourage a rethinking of the relationships between language and nationality, class, ethnicity, race, and gender. Highlighting perspectives from established and emerging researchers and drawing on a wide range of theoretical approaches and methodologies, the volume is organized around such key themes as bilingualism and diglossia; language variation across domains; language and identity in literature; and the interconnectedness of language, identity, and globalisation. Taken together, the collection calls attention to the socially and spatially situated nature of language practices in Bangladesh and in turn, the ways in which scholars in the Global South make sense of the sociolinguistic landscape at both the local and global level. This book will appeal to scholars working in sociolinguistics, particularly those working on language policy, language and identity, language variation, and in or about the Global South"--